Copper-cobalt bimetal Prussian blue analogue adsorbent, preparation method thereof and application of copper-cobalt bimetal Prussian blue analogue adsorbent in co-removal of ammonia gas and hydrogen sulfide gas at room temperature

By developing copper-cobalt bimetallic Prussian blue analog adsorbent, the competitive adsorption and poor structural stability of existing adsorbents at room temperature are solved, and efficient and stable co-removal effect is achieved, which is suitable for industrial applications.

CN119897057AActive Publication Date: 2025-04-29SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411953627.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-29
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

When the existing Prussian blue analog adsorbents simultaneously remove trace amounts of ammonia and hydrogen sulfide gas at room temperature, there are problems of competitive adsorption phenomena and poor structural stability, resulting in a degradation of adsorption performance.

Method used

A copper-cobalt bimetallic Prussian blue analog adsorbent was developed. By regulating the ratio of copper and cobalt, the number and size of hollows in the adsorbent were accurately controlled, forming a stable face-centered cubic structure, and enhancing the adsorption performance of ammonia and hydrogen sulfide.

Benefits of technology

It achieves efficient co-removal of trace ammonia and hydrogen sulfide at room temperature, maintains the sustainability and stability of adsorption performance, and is suitable for long-term needs in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897057A_ABST
    Figure CN119897057A_ABST
Patent Text Reader

Abstract

The invention provides a copper-cobalt bimetal Prussian blue analogue adsorbent, a preparation method thereof and application of the copper-cobalt bimetal Prussian blue analogue adsorbent in co-removal of ammonia gas and hydrogen sulfide gas at room temperature. The method comprises the following steps: (1) preparing a ligand solution; (2) preparing a mixed metal salt solution; and (3) synthesizing the copper-cobalt bimetal Prussian blue analogue. The copper-cobalt bimetal Prussian blue analogue prepared in the precipitation process can be used as a solid adsorbent for trace odorous ammonia gas and hydrogen sulfide, so that joint adsorption of two trace odorous gases is realized; moreover, the preparation method is simple, has the advantages of high adsorption efficiency, high stability and the like, is particularly suitable for the field of gas co-adsorption, and has wide application prospect and reference value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of odor gas adsorption and purification, and in particular to a copper-cobalt bimetallic Prussian blue analog adsorbent and a preparation method thereof, and application thereof in the co-removal of ammonia and hydrogen sulfide gases at room temperature. Background Art

[0002] The removal of trace odor gas pollutants at room temperature has always been an important topic in the field of environmental governance. In confined spaces such as sewage treatment plants, landfills, agricultural facilities (such as farm sheds) and submarines, there are often a variety of trace harmful odor gas pollution. These odorous gases not only cause environmental pollution, but also cause serious harm to human health. Ammonia (NH3) and hydrogen sulfide (H2S) are the two most common trace odor gas pollutants. Long-term exposure to low concentrations of ammonia and hydrogen sulfide may cause significant damage to the visual system and respiratory system, and even cause suffocation or death. According to the GJB 11B-2012 regulations designated by our country, the allowable concentration of hydrogen sulfide in a confined space cannot be higher than 0.07mg / m 3 The permissible concentration of ammonia cannot be higher than 3.5 mg / m 3 Therefore, developing efficient adsorbents that can simultaneously remove trace amounts of ammonia and hydrogen sulfide at room temperature is of vital importance for reducing environmental pollution and purifying the air. The adsorption method is widely used in the field of gas purification due to its advantages such as simple and effective process, low cost, environmental protection, and convenient operation. Among them, the development of adsorbents with high adsorption capacity, high selectivity, and good stability is the key to the adsorption method.

[0003] Traditional adsorbents such as carbon materials and molecular sieves mainly remove odorous gases through physical adsorption, and their adsorption capacity is limited. Prussian blue analogs show broad application prospects in the field of adsorption separation due to their ultra-high specific surface area, adjustable pore size, highly dispersed metal sites, and good thermal and chemical stability. Prussian blue analogs have simple cubic and nanoscale crystal structures, and linearly bridge octahedral metal ions through cyanide anions. In Prussian blue analog crystals, there are two types of adsorption sites for small molecule gases, namely interstitial sites and vacancy sites. Among them, vacancy sites are caused by the absence of [M(CN)6] units, and open metal sites are conducive to the highly selective capture of trace small molecule gases through coordination. Small molecule gases are mainly adsorbed on vacancies through coordination with metals. Too many vacancies may cause local instability or structural defects in the lattice, while too few vacancies may limit the improvement of adsorption performance. Traditional adsorbents such as carbon materials and molecular sieves mainly remove odorous gases by physical adsorption, and their adsorption capacity is limited. However, the metals at the vacancy sites of Prussian blue analogs can be complexed with target gases such as ammonia through complexation, thereby showing excellent adsorption performance. Akira Takahashi et al. reported that a traditional pigment Prussian blue PB had a static adsorption capacity of 12.5 mmol / g for ammonia adsorption at 0.1 MPa, which is greater than the amount of any traditional adsorbent (Takahashi Akira, et al. "Historical Pigment Exhibiting Ammonia Gas Capture beyond Standard Adsorbents with Adsorption Sites of Two Kinds." Journal of the American Chemical Society 138.20(2016):6376-9.). However, the Prussian blue analogs reported so far still have some shortcomings: (1) For Prussian blue analog adsorbents with a single metal site, when ammonia and hydrogen sulfide are present at the same time, competitive adsorption occurs, resulting in a significant decrease in adsorption performance compared to a single adsorption system. Specifically, ammonia molecules can coordinate with metal sites through nitrogen atoms, thereby occupying the active sites of the metal center in the Prussian blue analogue, and then competing with hydrogen sulfide for adsorption, inhibiting the adsorption of hydrogen sulfide. (2) Although high-density vacancy sites are beneficial to high adsorption capacity, too many vacancy sites will lead to local instability or structural defects in the lattice, resulting in poor material structural stability and easy collapse. Therefore, it is of great practical application and theoretical guidance to develop Prussian blue analogue adsorbents with more stable and efficient performance for the removal of trace odorous gases at room temperature and to further study their adsorption mechanism. Summary of the invention

[0004] In view of this, in order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a copper-cobalt bimetallic Prussian blue analog adsorbent and a preparation method thereof and an application for the co-removal of ammonia and hydrogen sulfide gas at room temperature. The copper-cobalt bimetallic Prussian blue analog adsorbent proposed in the present invention includes two metal sites, copper and cobalt, which can effectively adsorb and deeply remove low-concentration ammonia and hydrogen sulfide. At the same time, the adsorbent can maintain a stable face-centered cubic structure during the adsorption process, ensuring the continuity and stability of the adsorption performance. The use of the adsorbent for gas removal treatment not only has good green economic benefits, but also has excellent performance stability, and can meet the long-term needs in industrial applications.

[0005] In order to achieve the purpose of the above invention, the present invention provides the following technical solutions:

[0006] A copper-cobalt bimetallic Prussian blue analogue adsorbent for co-removing ammonia and hydrogen sulfide gas at room temperature. The basic structure of the copper-cobalt bimetallic Prussian blue analogue adsorbent consists of metal ions and ligands, the molar ratio of the metal ions to the ligands is 1.5-3.0; the metal ions are copper ions and cobalt ions; and the ligands are cyanide salts.

[0007] Preferably, the copper-cobalt bimetallic Prussian blue analog adsorbent contains two metal ion sites, copper ion and cobalt ion, and the molar ratio of copper ion to cobalt ion is at least one of 1:5, 1:2, 1:1, 2:1, and 5:1.

[0008] Preferably, the cyanide salt is at least one of potassium cobalt cyanide, potassium iron cyanide, potassium nickel cyanide, and potassium manganese cyanide. The cyanide ion (CN-) in the cyanide salt acts as a bridging agent and forms a three-dimensional network structure by coordinating with metal ions.

[0009] Preferably, the metal salt is derived from at least one of chloride, sulfate and nitrate.

[0010] Preferably, the specific surface area of ​​the copper-cobalt bimetallic Prussian blue analog adsorbent is 500 to 1000 m 2 / g, the micropore size distribution is 0.5-1nm, and it contains mesopores and macropores.

[0011] A method for preparing a copper-cobalt bimetallic Prussian blue analog adsorbent, the preparation method comprising the following steps:

[0012] (1) Preparation of ligand solution: Dissolve the ligand in a solvent and dissolve by ultrasonication to obtain solution A;

[0013] (2) Preparation of a mixed metal salt solution: 0.01-0.05 mol / L copper metal salt and cobalt metal salt are mixed and dissolved in a solvent, and ultrasonically dissolved to obtain a solution B;

[0014] (3) Solution A in step (1) is mixed with solution B in step (2), stirred in a water bath for reaction at a speed of 300 to 1000 rpm, allowed to stand for aging for 24 hours, centrifuged 4 to 6 times, washed with deionized water and anhydrous ethanol, dried in a vacuum drying oven at 80° C. for 12 to 24 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analog.

[0015] Preferably, in step (1) and step (2), the solvent is at least one of deionized water, ethanol, ethylene glycol, sodium citrate, and N,N-dimethylformamide (DMF), and the concentration of the solvent is 5% to 80% (excluding deionized water). Different solvents will affect the growth process of the crystal, thereby affecting the morphology and size of the crystal.

[0016] Preferably, in step (1) and step (2), the concentration of the ligand in solution A is 0.01 to 0.04 mol / L.

[0017] Preferably, the molar ratio of copper ions:cobalt ions in step (2) is at least one of 1:5, 1:2, 1:1, 2:1, and 5:1.

[0018] Preferably, the water bath stirring temperature in step (3) is 25-80°C.

[0019] Preferably, the water bath stirring time in step (3) is 12 to 24 hours.

[0020] An application of the copper-cobalt bimetallic Prussian blue analogue adsorbent as described above, the application is for the co-removal of low-concentration ammonia and hydrogen sulfide gases at room temperature.

[0021] Preferably, the concentration of trace hydrogen sulfide is in the range of 5 to 100×10 -6 mol / mol-air; the concentration range of trace ammonia is 1000~5000×10 -6 mol / mol-air.

[0022] The present invention provides a method for preparing a copper-cobalt bimetallic Prussian blue analog adsorbent for co-removing ammonia (NH3) and hydrogen sulfide (H2S) gas at room temperature. The method adopts a liquid coprecipitation method, mixes metal salt solutions with ligand solutions in different molar ratios, and prepares a copper-cobalt bimetallic Prussian blue analog through a precipitation reaction. By adjusting the ratio of copper and cobalt metals, the number and size of vacancies in the Prussian blue analog are precisely controlled, thereby optimizing its adsorption performance and structural stability for ammonia and hydrogen sulfide. The adsorbent not only has a simple preparation process, but also exhibits excellent adsorption efficiency and high stability, and has a wide range of application potentials.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] (1) The present invention introduces bimetallic adsorption sites that have strong adsorption effects on ammonia and hydrogen sulfide on the Prussian blue analog adsorbent, thereby effectively solving the problem of competitive adsorption of hydrogen sulfide and ammonia on the same metal site, thereby achieving efficient co-removal of hydrogen sulfide and ammonia.

[0025] (2) The copper-cobalt bimetallic Prussian blue analog adsorbent prepared by the present invention has excellent structural stability. By precisely adjusting the ratio of copper and cobalt metals and the vacancy characteristics, the structural stability of the adsorbent during long-term use is ensured, and the problem of performance degradation of traditional adsorbents due to structural changes during cyclic use is avoided. This structural stability enables the adsorbent of the present invention to continue to maintain efficient adsorption performance in long-term applications, meeting the requirements for long-term performance and stability at room temperature.

[0026] (3) The copper-cobalt bimetallic Prussian blue analog adsorbent prepared by the present invention has the advantages of high initial purification efficiency (≥95%) for trace ammonia (NH3) and hydrogen sulfide (H2S) under normal temperature and pressure conditions and high penetration adsorption capacity (NH3≮149.6mg / g; H2S≮28.8mg / g). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 1 is the X-ray diffraction pattern of the copper-cobalt bimetallic Prussian blue analog adsorbent prepared in Examples 1 to 5.

[0028] Figure 2 This is the NH3 breakthrough curve of the copper-cobalt bimetallic Prussian blue analog adsorbent prepared in Examples 1 to 5 at normal temperature and pressure.

[0029] Figure 3 This is the H2S breakthrough curve of the copper-cobalt bimetallic Prussian blue analog adsorbent prepared in Examples 1 to 5 at normal temperature and pressure.

[0030] Figure 4 3 is the XRD pattern of the copper-cobalt bimetallic Prussian blue analogue adsorbent prepared in Example 2 before and after adsorbing NH3 and H2S.

[0031] Figure 5 This is the XRD diagram of the copper-cobalt bimetallic Prussian blue analog adsorbent prepared in Comparative Example 1 before and after adsorbing NH3 and H2S.

[0032] Figure 6 It is the H2S breakthrough curve of the copper-cobalt bimetallic Prussian blue analog adsorbent prepared in Example 2 and Comparative Example 2 under normal temperature and pressure conditions. DETAILED DESCRIPTION

[0033] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0034] Example 1

[0035] 3.2 mmol of potassium cobalt cyanide was dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution A; 1.6 mmol of copper chloride and 3.2 mmol of cobalt chloride were mixed and dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution B; solution B was added dropwise into solution A and mixed therewith, stirred at a water bath temperature of 25°C for 12 to 24 hours at a rotation speed of 300-500 rpm, allowed to stand for aging for 24 hours, then transferred to a centrifuge tube and centrifuged, then washed with deionized water for 4 to 5 times, 30 ml each time, washed once with anhydrous ethanol, dried in a vacuum drying oven at 80°C for 12 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analogue, recorded as sample #1.

[0036] Example 2

[0037] 3.2 mmol of potassium cobalt cyanide was dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution A; 2.4 mmol of copper chloride and 2.4 mmol of cobalt chloride were mixed and dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution B; solution B was added dropwise into solution A and mixed therewith, stirred at a water bath temperature of 25°C for 12 to 24 hours at a rotation speed of 300-500 rpm, allowed to stand for aging for 24 hours, then transferred to a centrifuge tube for centrifugation, then washed with deionized water for 4 to 5 times, 30 ml each time, washed once with anhydrous ethanol, dried in a vacuum drying oven at 80°C for 12 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analogue, recorded as sample #2.

[0038] Example 3

[0039] 3.2 mmol of potassium cobalt cyanide was dissolved in 50 mL of 70% ethylene glycol solution and dissolved by ultrasonication to obtain solution A; 2.4 mmol of copper chloride and 2.4 mmol of cobalt chloride were mixed and dissolved in 50 mL of 70% ethylene glycol solution and dissolved by ultrasonication to obtain solution B; solution B was added dropwise into solution A and mixed therewith, stirred at a water bath temperature of 25°C for 12 to 24 hours at a rotation speed of 300-500 rpm, allowed to stand for aging for 24 hours, then transferred to a centrifuge tube for centrifugation, washed with deionized water for 4 to 5 times, 30 ml each time, washed once with anhydrous ethanol, dried in a vacuum drying oven at 80°C for 12 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analogue, recorded as sample #3.

[0040] Example 4

[0041] 3.2 mmol of potassium cobalt cyanide was dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution A; 3.2 mmol of copper chloride and 1.6 mmol of cobalt chloride were mixed and dissolved in 50 mL of aqueous solution and dissolved by ultrasonication to obtain solution B; solution B was added dropwise into solution A and mixed therewith, stirred at a water bath temperature of 25°C for 12 to 24 hours at a rotation speed of 300-500 rpm, allowed to stand for aging for 24 hours, then transferred to a centrifuge tube and centrifuged, then washed with deionized water for 4 to 5 times, 30 ml each time, washed once with anhydrous ethanol, dried in a vacuum drying oven at 80°C for 12 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analogue, recorded as sample #4.

[0042] Example 5

[0043] 3.2 mmol of potassium cobalt cyanide was dissolved in 50 mL of 8% sodium citrate solution and dissolved by ultrasonication to obtain solution A; 2.4 mmol of copper chloride and 2.4 mmol of cobalt chloride were mixed and dissolved in 50 mL of 8% sodium citrate solution and dissolved by ultrasonication to obtain solution B; solution B was added dropwise into solution A and mixed therewith, stirred at a water bath temperature of 25°C for 12 to 24 hours at a rotation speed of 300-500 rpm, allowed to stand for aging for 24 hours, then transferred to a centrifuge tube for centrifugation, washed with deionized water for 4 to 5 times, 30 ml each time, washed once with anhydrous ethanol, dried in a vacuum drying oven at 80°C for 12 hours, and ground to obtain a powdered copper-cobalt bimetallic Prussian blue analogue, recorded as sample #5.

[0044] Effect Example

[0045] like Figure 1 As shown, Figure 1 It is the XRD pattern of the copper-cobalt bimetallic Prussian blue analogue prepared in Examples 1 to 5. It can be seen from the figure that the obtained material has characteristic peaks at 16.9°, 24.4°, 35.0°, 39.1°, 43.1°, 50.3°, 53.6°, and 56.7°, and the overall peak position is between Cu-PBA (JCPDS: 02-0169) and Co-PBA (JCPDS: 22-0215). These characteristic peaks are respectively attributed to (200), (220), (400), (420), (422), (440), (600), and (620) crystal plane diffraction peaks, and the diffraction peaks of the material are strong and the half-peak width is narrow, indicating that the copper-cobalt bimetallic Prussian blue analogue with good crystallinity has been successfully synthesized.

[0046] The adsorption effects of Examples 1 to 5 on 3000 ppm ammonia and 50 ppm hydrogen sulfide were compared, and the penetration capacity of each material was obtained as shown in Table 1.

[0047] Table 1 Breakthrough adsorption capacity of NH3 and H2S in Examples 1 to 5

[0048]

[0049]

[0050] like Figure 2 As shown, Figure 2 The ammonia permeation curves of the copper-cobalt bimetallic Prussian blue analogs prepared in Examples 1 to 5 at room temperature and pressure, with the NH3 concentration being 3000×10 -6 mol / mol-air. The time required for the outlet concentration to reach 5% of the initial concentration is set as the breakthrough time, and the corresponding adsorption capacity is the permeation adsorption capacity. In Examples 1 to 5, the breakthrough times are 103.7, 73.6, 96.2, 66.2, and 88.7 min, respectively, and the corresponding NH3 permeation adsorption capacities are 13.9, 9.7, 12.8, 8.8, and 11.8 mmol / g, respectively. It can be seen from the results that the copper-cobalt bimetallic Prussian blue analogue of the present invention can effectively purify trace amounts of NH3. Among them, the copper-cobalt bimetallic Prussian blue analogue in Example 1 shows a more excellent adsorption capacity than that in Examples 2 and 4. This is because Example 1 has more cobalt metal adsorption sites, and the surface properties and electronic structure of cobalt enable it to cooperate with more NH3, thereby increasing the adsorption amount of NH3.

[0051] like Figure 3 As shown, Figure 3 The hydrogen sulfide permeation curves of the copper-cobalt bimetallic Prussian blue analogs prepared in Examples 1 to 5 at room temperature and pressure, with a H2S concentration of 50×10 -6 mol / mol-air. The time required for the outlet concentration to reach 5% of the initial concentration is set as the breakthrough time, and the corresponding adsorption capacity is the permeation capacity. In Examples 1, 2, 3, 4, and 5, the breakthrough times are 441.9, 387.9, 429.4, 335.6, and 399.2 min, respectively, and the corresponding H2S permeation adsorption capacities are 1.18, 1.04, 1.15, 0.90, and 1.07 mmol / g, respectively. It can be seen from the results that the copper-cobalt bimetallic Prussian blue analogue of the present invention can effectively purify trace amounts of H2S.

[0052] like Figure 4 As shown, Figure 4 1 is the XRD pattern of the copper-cobalt bimetallic Prussian blue analogue prepared in Example 2 before and after adsorbing NH3 and H2S. It can be seen that the structure of the copper-cobalt bimetallic Prussian blue analogue prepared in Example 2 remains unchanged after adsorbing NH3 and H2S, and the diffraction peak intensity of the material remains almost unchanged, indicating that the copper-cobalt bimetallic Prussian blue analogue can maintain strong structural stability during the adsorption process.

[0053] In order to further illustrate the superiority of the present application, the present application also provides the following comparative examples.

[0054] Comparative Example 1

[0055] The difference between Comparative Example 1 and Example 2 is that only copper chloride solution and potassium cobalt cyanide solution are used to react to obtain a copper Prussian blue analog adsorbent. The adsorption performance of the adsorbent for ammonia and hydrogen sulfide was tested, and it was found that the structure of the copper Prussian blue analog adsorbent changed after adsorbing ammonia, and the structure almost collapsed after adsorbing hydrogen sulfide, such as Figure 5 It can be seen from the above examples and comparative examples that the copper-cobalt bimetallic Prussian blue analog adsorbent for achieving co-removal of low-concentration ammonia and hydrogen sulfide at room temperature and pressure provided by the present invention has strong structural stability.

[0056] Comparative Example 2

[0057] The difference between Comparative Example 2 and Example 2 is that only cobalt chloride solution and potassium cobalt cyanide solution are mixed to obtain a cobalt Prussian blue analog adsorbent. The adsorption performance of the adsorbent for ammonia and hydrogen sulfide was tested, and it was found that the adsorbent had poor performance in removing hydrogen sulfide after adsorbing ammonia, which was significantly lower than the adsorption effect of Example 2. Figure 6 This is because the adsorbed ammonia has a strong complexation with metal cobalt, which almost occupies all the metal cobalt active sites of the adsorbent, resulting in the inability of hydrogen sulfide to continue to react chemically with the metal sites, thereby reducing the adsorption performance.

[0058] Comparative Example 3

[0059] Compared with Example 2, the difference in Comparative Example 3 is that the sum of the amounts of copper chloride and cobalt chloride is 2.4 mmol, which is only half of that in Example 2, does not meet the stoichiometric ratio and is less. The other conditions are the same as in Example 2, and a copper-cobalt Prussian blue analog adsorbent is prepared. It was found that due to the low amount of copper chloride and cobalt chloride, potassium cobalt cyanide could not react with sufficient copper ions and cobalt ions, resulting in a decrease in the conversion rate of the reactants and a decrease in the yield of the generated copper-cobalt Prussian blue analog. The ammonia and hydrogen sulfide adsorption penetration curves of the bimetallic copper-cobalt Prussian blue analog adsorbent were tested, and it was found that the penetration adsorption capacity of ammonia and hydrogen sulfide was lower than that of Example 2, because when the proportion of metal salt is low, it may lead to a reduction or incomplete formation of adsorption sites, thereby reducing the specific surface area of ​​the final product and weakening the adsorption performance.

[0060] Comparative Example 4

[0061] Compared with Example 2, the difference of Comparative Example 4 is that the stirring time of solution A and solution B is 10 minutes, and the other conditions are the same as those of Example 2, and a copper-cobalt Prussian blue analog adsorbent is prepared. It can be seen that the diffraction peak intensity of the XRD pattern of the product is significantly low. This is because the reaction time is too short, and the generated Prussian blue analog may not be fully crystallized, or the crystal structure is incomplete, resulting in irregular crystal morphology of the product, or even presenting as amorphous or amorphous substances. And the ammonia and hydrogen sulfide adsorption penetration curves of the bimetallic copper-cobalt Prussian blue analog adsorbent are tested, and it is found that the penetration adsorption capacity of ammonia and hydrogen sulfide is lower than that of Example 2. This is because the shorter reaction time may lead to incomplete crystal growth, forming smaller or uneven particles, and ultimately reducing the specific surface area, which directly leads to a decrease in the adsorption performance of the Prussian blue analog.

Claims

1. A copper-cobalt bimetallic Prussian blue analog adsorbent, characterized in that: The basic structure of the copper-cobalt bimetallic Prussian blue analogue adsorbent consists of metal ions and ligands, the molar ratio of the metal ions to the ligands is 1.5-3.0; the metal ions are copper ions and cobalt ions; and the ligands are cyanide salts.

2. A copper-cobalt bimetallic Prussian blue analog adsorbent as claimed in claim 1, characterized in that: The copper-cobalt bimetallic Prussian blue analogue adsorbent comprises two metal ion sites, namely copper ion and cobalt ion, and the molar ratio of copper ion to cobalt ion is at least one of 1:5, 1:2, 1:1, 2:1 and 5:

1.

3. A copper-cobalt bimetallic Prussian blue analog adsorbent as claimed in claim 1, characterized in that: The cyanide salt is at least one of potassium cobalt cyanide, potassium iron cyanide, potassium nickel cyanide, and potassium manganese cyanide.

4. A copper-cobalt bimetallic Prussian blue analog adsorbent as claimed in claim 1, characterized in that: The metal ions are derived from at least one of chloride, sulfate and nitrate.

5. The copper-cobalt bimetallic Prussian blue analog adsorbent according to claim 1, characterized in that: The specific surface area of ​​the copper-cobalt bimetallic Prussian blue analog adsorbent is 500 to 1000 m 2 / g, the micropore size distribution is 0.5-1nm, and it contains mesopores and macropores.

6. The method for preparing a copper-cobalt bimetallic Prussian blue analog adsorbent according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Preparation of ligand solution: dissolving the ligand in a solvent and dissolving by ultrasonication to obtain solution A; Step 2: Preparation of a mixed metal salt solution: 0.01-0.05 mol / L copper metal salt and cobalt metal salt are mixed and dissolved in a solvent, and ultrasonically dissolved to obtain a solution B; Step 3: Mix solution A and solution B, stir in a water bath to react, the rotation speed is 300-1000 rpm, stand for aging for 12-24 hours, centrifuge 4-6 times, wash with deionized water and anhydrous ethanol, dry in a vacuum drying oven at 60-80°C for 12-24 hours, grind to obtain a powdered copper-cobalt bimetallic Prussian blue analogue.

7. The preparation method according to claim 6, characterized in that: In step 1 and step 2, the solvent is at least one of deionized water, ethanol, ethylene glycol, sodium citrate, and N,N-dimethylformamide (DMF), and the mass percentage concentration of the solvent other than deionized water is 5% to 80%.

8. The preparation method according to claim 6, characterized in that: In step 1 and step 2, the concentration of the ligand in the solution A is 0.01-0.04 mol / L.

9. The preparation method according to claim 6, characterized in that: In step 3, the water bath stirring temperature ranges from 25 to 80° C. and the stirring time is 12 to 24 hours.

10. A use of a copper-cobalt bimetallic Prussian blue analog adsorbent as claimed in any one of claims 1 to 5, characterized in that: It is used for the simultaneous high-efficiency adsorption and purification of trace odorous gases hydrogen sulfide and ammonia at room temperature, and the concentration range of the trace hydrogen sulfide is 5 to 100×10 -6 mol / mol-air; the concentration range of trace ammonia is 1000~5000×10 -6 mol / mol-air.

Citation Information

Patent Citations

  • Method for preparing hierarchical bimetallic composite oxide denitrification catalyst

    CN103752321A

  • Preparation method of prussian-blue compound ammonium removal material, and application of prussian-blue compound ammonium removal material in removing ammonium from sewage

    CN107486130A

  • Carbon-based Prussian blue analogue composite material, preparation method and applications thereof

    CN110540216A

  • Mesh cross-linked gel as well as preparation method and application thereof

    CN115400733A

  • Supported compound activated carbon fiber paper composite adsorbent for removing trace odorous gas at room temperature as well as preparation method and application of supported compound activated carbon fiber paper composite adsorbent

    CN115888670A

Cited By

  • Preparation method and application of oversized metal ferrocyanide

    CN120423575A